Implementation of Cooperative Learning Model to Improve Critical Thinking and Student Learning Outcomes at SDN Mertasinga 07 Cilacap Utara - Dwi Setyaningsih; Sriyanto Sriyanto (Proceedings Series on Social Sciences & Humanities, 2025)
This study aims to investigate the impact of cooperative learning models on improving critical thinking skills and student learning outcomes at SDN Mertasinga 07, North Cilacap. Using a descriptive qualitative case study approach, data were collected through literature review, interviews, observations, and document analysis. The study found that cooperative learning models, such as Jigsaw and Student Teams Achievement Division (STAD), significantly enhance students’ engagement, conceptual understanding, and critical thinking capabilities. These improvements positively influence learning outcomes. The implementation process, challenges encountered, and proposed solutions are discussed in detail. The study recommends that primary school teachers actively integrate cooperative learning models into their pedagogical strategies to foster higher-order thinking and academic achievement. The results of the study show that the cooperative learning model has a significant positive impact on students' critical thinking skills. Students become more active in class discussions, show improvement in evaluating information, and are more confident in presenting their ideas. Furthermore, cooperative learning also improves academic performance by creating a collaborative and student-centered learning environment that supports motivation and deeper understanding.Based on the findings, the cooperative learning model is recommended as an effective instructional approach to be integrated into elementary school learning, especially to develop students’ 21st-century competencies.